Social and economic upgrading in floriculture global value chains : flowers and cuttings GVCs in Uganda /: flowers and cuttings GVCs in Uganda. (June 2014) - (Research fellow), Evers, Barbara; Amoding, Flavia; Krishnan, Aarti
No abstract available